Perubahan Anti Nutrisi pada Silase Buah Semu Jambu Mete sebagai Pakan dengan menggunakan Berbagai Aras Tepung Gaplek dan Lama Pemeraman (Change of Antinutritive Value of Chestnut Fruit (Anacardium occidentale) Silage in Combination with Various Level of - Bernadete Barek Koten (Buletin Peternakan, 2010)
The objective of this experiment was to evaluate antinutritive value of chestnut fruit silage in combination with various level of cassava meal addition and time of fermentation. The study was conducted for 8 month at Ratulodongcountryside, district of Tanjung Bunga and at Nutrition and Fodder Laboratory. This experiment was conducted in 2 treatment factors with 3 replication. The first factor was various level of cassava meal e.i. 0, 3, 6, and 9%, and thesecond factor was time of fermentation e.i. 20, 40, and 60 days. The result showed that silage technonogy with various cassava meal level and fermentation time significantly (P<0.01) decreased antinutritive value of chestnut fruit. Tannincontent decreased in line with increasing level of cassava meal and time of fermentation. Higher tannin at 0% cassava meal with fermentation time of 20 days (0.35%), and lower at 3% cassava meal with fermentation time of 40 days(0.06%). The highest phytic acid content at 9% cassava meal with fermentation time of 40 days (5.48%), and the lowest at 6% cassava meal with fermentation time of 20 days (2.38%). Tannin and phytic acid content were decreased duringfermentation process and lower than fresh fruit chestnut. It could be concluded that silage technonogy could be applied at chestnut fruit. This technology increased the benefit of chestnut fruit as feed ingredient because it decreasedantinutritive value. The lowest antinutritive value at 0% cassava meal with fermentation time of 60 days.(Key words: Silage, Chestnut fruit, Cassava meal, Fermentation time, Tannin, Phytic acid)